Clinical implications of trials investigating drug‐drug interactions between cannabidiol and enzyme inducers or inhibitors or common antiseizure drugs. (12th September 2020) - Patsalos, Philip N.; Szaflarski, Jerzy P.; Gidal, Barry; VanLandingham, Kevan; Critchley, David; Morrison, Gilmour
Abstract: Highly purified cannabidiol (CBD) has demonstrated efficacy with an acceptable safety profile in patients with Lennox‐Gastaut syndrome or Dravet syndrome in randomized, double‐blind, add‐on, controlled phase 3 trials. It is important to consider the possibility of drug‐drug interactions (DDIs). Here, we review six trials of CBD (Epidiolex/Epidyolex; 100 mg/mL oral solution) in healthy volunteers or patients with epilepsy, which investigated potential interactions between CBD and enzymes involved in drug metabolism of common antiseizure drugs (ASDs). CBD did not affect CYP3A4 activity. Induction of CYP3A4 and CYP2C19 led to small reductions in exposure to CBD and its major metabolites. Inhibition of CYP3A4 activity did not affect CBD exposure and caused small increases in exposure to CBD metabolites. Inhibition of CYP2C19 activity led to a small increase in exposure to CBD and small decreases in exposure to CBD metabolites. One potentially clinically important DDI was identified: combination of CBD and clobazam (CLB) did not affect CBD or CLB exposure, but increased exposure to major metabolites of both compounds. Reduction of CLB dose may be considered if adverse reactions known to occur with CLB are experienced when it is coadministered with CBD. There was a small increase of exposure to stiripentol (STP) when coadministered with CBD. STP had no effect on CBD exposure but led to minor decreases in exposure to CBD metabolites. Combination of CBD and valproate (VPA) did not cause clinically important changes in the pharmacokinetics of either drug, or 2‐propyl‐4‐pentenoic acid. Concomitant VPA caused small increases in exposure to CBD metabolites. Dose adjustments are not likely to be necessary when CBD is combined with STP or VPA. The safety results from these trials were consistent with the known safety profile of CBD. These trials indicate an overall low potential for DDIs between CBD and other ASDs, except for CLB.